Design of a full W‐band detector based on Schottky diode with quartz substrate. Issue 7 (14th March 2019) - Guo, Jian; Cheng, Haifeng; Xu, Jie; Qian, Cheng
Abstract : A power detector based on Schottky diode with a quartz substrate is proposed in this study. A three‐dimensional model of the Schottky diode is built for accurate performance evaluation. A broadband input DC grounding circuit is designed based on two sets of radial stubs. An output chocking circuit is implemented using a single compact microstrip resonator cell, which features compact size and broad stopband. Input and output matching circuits are also introduced to achieve flat frequency response. Measured results agree well with simulated ones. The voltage sensitivity is about 6000–9500 mV/mW with −30 dBm drive power at the full W‐band (75–110 GHz). The detector also has outstanding temperature stability. The output voltage varies <6.3% with −3 dBm drive power when ambient temperature changes from −40 to +60°C.